Women entrepreneurs’ learning experiences in securing microcredit and establishing a business - Ergüney, Deniz İrem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
Microcredit programs, which are seen as a solution to eliminating poverty in the world in addition to the economic liberation of women, have become widespread in countries. There are studies that show that these programs have positive effects on women and support women's empowerment, as well as studies claiming the opposite. Considering the studies conducted in this field, there is no study examining the experiences of women entrepreneurs throughout the whole process from the perspective of adult education. The aim of this qualitative research is to examine the learning experiences of women who received training from KOSGEB. Then, opened their workplaces with credit support. Semi-structured interviews were carried out with women entrepreneurs from Lüleburgaz who started their own businesses with credit support from KOSGEB. The results of the study shows that participants found the entrepreneurship training provided by KOSGEB very efficient. There were differences regarding the duration of the training as the participants attended training at different time periods and institutions. Most participants stated that they had a lot of trouble in the process of renting the shop and making expenses before receiving the loan. The fact that KOSGEB gives the loan after the establishment of the enterprises and the intensive inspections and paperwork carried out in this process challenged the participants. All participants stated that their lives improved positively after starting their own businesses. 11 of the 12 participants stated that they did not regret applying for a KOSGEB credit despite the difficulties they experienced during the process.
Keywords: Microfinance -- Turkey.; Women -- Turkey -- Economic conditions.; Women -- Turkey -- Social conditions.; Women in development -- Turkey.